Cancellous bone-like porous Fe@Zn scaffolds with core-shell-structured skeletons for biodegradable bone implants. (February 2021) - He, Jin; Fang, Ju; Wei, Pengbo; Li, Yulei; Guo, Hui; Mei, Qingsong; Ren, Fuzeng
Abstract: Three-dimensional (3D) porous zinc (Zn) with a moderate degradation rate is a promising candidate for biodegradable bone scaffolds. However, fabrication of such scaffolds with adequate mechanical properties remains a challenge. Moreover, the composition, crystallography and microstructure of the in vivo degradation products formed at or near the implant-bone interface are still not precisely known. Here, we have fabricated porous Fe@Zn scaffolds with skeletons consisting of an inner core layer of Fe and an outer shell layer of Zn using template-assisted electrodeposition technique, and systematically evaluated their porous structure, mechanical properties, degradation mechanism, antibacterial ability and in vitro and in vivo biocompatibility. In situ site-specific focused ion beam micromilling and transmission electron microscopy were used to identify the in vivo degradation products at the nanometer scale. The 3D porous Fe@Zn scaffolds show similar structure and comparable mechanical properties to human cancellous bone. The degradation rates can be adjusted by varying the layer thickness of Zn and Fe. The antibacterial rates reach over 95% against S. aureus and almost 100% against E. coli . A threshold of released Zn ion concentration ( 0.3 mM) was found to determine the in vitro biocompatibility. Intense new bone formation and ingrowth were observed despite with a slight inflammatory response. The in vivo degradation products were identified to be equiaxed nanocrystalline zinc oxide with dispersed zinc carbonate. This study not only demonstrates the feasibility of porous Fe@Zn for biodegradable bone implants, but also provides significant insight into the degradation mechanism of porous Zn in physiological environment. Graphical abstract: Image, graphical abstract